Authentic leadership, trust and work engagement - Hassan, Arif; Ahmed, Forbis (World Academy of Science, Engineering and Technology (W A S E T), 2011)
The issue of leadership has been investigated from several perspectives; however, very less from ethical perspective. With the growing number of corporate scandals and unethical roles played by business leaders in several parts of the world, the need to examine leadership from ethical perspective cannot be over emphasized. The importance of leadership credibility has been discussed in the authentic model of leadership. Authentic leaders display high degree of integrity, have deep sense of purpose, and committed to their core values. As a result they promote a more trusting relationship in their work groups that translates into several positive outcomes. The present study examined how authentic leadership contribute to subordinates’ trust in leadership and how this trust, in turn, predicts subordinates’ work engagement. A sample of 395 employees was randomly selected from several local banks operating in Malaysia. Standardized tools such as ALQ, OTI, and EEQ were employed. Results indicated that authentic leadership promoted subordinates’ trust in leader, and contributed to work engagement. Also, interpersonal trust predicted employees’ work engagement as well as mediated the relationship between this style of leadership and employees’ work engagement.